Passaporte científico: uma atividade lúdica de reforço na aprendizagem - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Today, chemistry teachers seek methodologies to encourage students to understand their content. Using playful methodology within the school environment as a game is a very valuable tool, as it is a pleasant activity for students who without realizing it motivates them to learn. Remembering that one of the difficulties of students is to contextualize the chemistry within their daily life, even if the teacher exemplifies. Thus, this work aims at a game of chemistry, on balancing equations, with contextualized charts. Another advantage is that the game's card-making material has been to reuse cardboard boxes, printed sheets and contact paper to increase its durability. The activity should be planned by the teacher so that the learning objective occurs and through this tool the students demonstrate more interested in learning and participating in the activities in the classes of chemistry.
Scientific passport: a playful activity to reinforce learning
Keywords: Ciências da natureza; Natural sciences; Química; Balanceamento de equações; Game; Play activities; Chemistry; Balancing equations; CNPQ::CIENCIAS EXATAS E DA TERRA